METHODOLOGICAL DIVERSITY IN MICRO-CT EVALUATION OF BONE MICRO-ARCHITECTURE: IMPORTANCE FOR INTERSTUDY COMPARABILITY: COULD THE METHODOLOGICAL DIVERSITY OF MICRO-CT BONE EVALUATION BE AN ISSUE IN INTERSTUDY COMPARISON? - Andjelic, Uros; Djuric, Marija; Jadzic, Jelena (Medical Research, 2024)
Introduction: Micro-computed tomography (micro-CT) is a standard 3D technique for non-destructive analysis of bone micro-architecture. Although many micro-CT studies have been available in contemporary literature, interstudy comparability is often challenging due to a lack of method standardization, particularly regarding human bone analyses. Aim: This study aimed to assess the consistency of micro-CT generated micro-architectural parameters obtained by two researchers (interobserver reliability), by one researcher in two attempts (intraobserver reliability) as well as between manual and semi-automatic determination of the region of interest (ROI). Material and methods: Superolateral femoral neck samples (n=8) were scanned with Bruker 1172 micro-CT system with a voxel size of 10 µm. We manually determined cortical and trabecular ROI (two authors, two attempts with a 45-day span). Also, trabecular ROI was determined using a semi-automatic method (round-shaped ROI with a diameter of 6.5 mm). Results: The intraclass correlation coefficient (ICC) showed a high degree of consistency in the measurement of micro-architectural parameters of the superolateral femoral neck using the micro-CT (ICC range: 0.721-0.998; p<0.05). However, detailed analysis revealed significant interobserver and intraobserver differences, predominantly reflected in cortical porosity parameters (Student’s t-test for dependent samples, p<0.05). On the other hand, the choice of ROI did not significantly affect trabecular micro-architectural parameters among researchers and between manual and semi-automatic demarcation methods (Student’s t-test for dependent samples, p>0.05). Conclusion: Our study emphasizes the importance of standardizing the methodology used in micro-CT evaluations of human bone samples, which could facilitate reliable interstudy comparison and ensure adequate results interpretation.